Design and validation of a multidimensional questionnaire to assess adaptation to illness in onco-hematological patients (CMAE-OH) - Ulla, Sara; Arranz, Pilar (Psicooncología, 2008)
The main objective of this research was to design and develop an instrument suitable for the psychological assessment of hospitalised hematooncological patients; capable of providing answers to the needs arose. A questionnaire was designed; it should be assessed through a semi-structured interview. Three studies were conducted: a) An expert analysis of the content reliability of the fi rst version of the instrument, including qualitative and quantitative methodology; b) A pilot study to test the interview structure and consider other possible pitfalls in the data collecting process; c) An extensive assessment of 168 hematooncological patients in a University Hospital with the fi nal version of the assessment instrument. The instrument presented an adequate reliability level. We observed that it provided enough information for a preventive intervention, and it could also be used as a screening tool for the assessment of issues related to the adjustment to illness.